Human rights, COVID-19, and barriers to safe water and sanitation among people experiencing homelessness in Mexico City - Liera, Carla; Dickin, Sarah; Rishworth, Andrea; Bisung, Elijah; Moreno, Alexia; Elliott, Susan J. (Frontiers in Water, 2023)
Access to safe water, sanitation, and hygiene (WASH) are human rights and play a fundamental role in protecting health, which has been particularly evident during the SARS-CoV2 (Covid-19) pandemic. People experiencing homelessness face frequent violations of their human rights to water and sanitation, negatively affecting their health and dignity and ability to protect themselves from Covid-19. This research aimed to identify barriers to safe water, sanitation and hygiene access for people experiencing homelessness in Mexico City during the Covid-19 pandemic. A survey of 150 respondents experiencing homelessness was conducted using mobile data collection tools in collaboration with El Caracol A.C., an NGO that contributes to the visibility and social inclusion of homeless people in Mexico. We report findings according to the following themes: general economic impacts of Covid-19; experiences with reduced access to WASH services due to Covid-19, challenges in accessing hand washing to follow Covid-19 public health advice; and coping mechanisms used to deal with reductions in access to WASH. We discuss the broader implications of the findings in terms of realization of the human rights to water and sanitation (HRtWS), and how people experiencing homelessness are left behind by the existing approaches to ensure universal access to water and sanitation under SDG 6.